2009
DOI: 10.1002/hep.23481
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus gene repair corrects a mouse model of hereditary tyrosinemia in vivo

Abstract: Adeno-associated virus (AAV) vectors are ideal for performing gene repair due to their ability to target multiple different genomic loci, low immunogenicity, capability to achieve targeted and stable expression through integration, and low mutagenic and oncogenic potential. However, many handicaps to gene repair therapy remain. Most notable is the low frequency of correction in vivo. To date, this frequency is too low to be of therapeutic value for any disease. To address this, a point-mutation– based mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 42 publications
3
121
1
5
Order By: Relevance
“…3). The frequency of Afp + foci was similar to that observed when targeting other genes in prior AAV experiments (20,21), suggesting that each targeting event produced a single Afp + hepatocyte that proliferated to form an HCC focus. If additional spontaneous oncogenic mutations were required they must have consistently occurred before each ∼1,000 cell malignancy developed.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…3). The frequency of Afp + foci was similar to that observed when targeting other genes in prior AAV experiments (20,21), suggesting that each targeting event produced a single Afp + hepatocyte that proliferated to form an HCC focus. If additional spontaneous oncogenic mutations were required they must have consistently occurred before each ∼1,000 cell malignancy developed.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that in addition to their potential for random, nonhomologous integration, AAV vectors can efficiently and accurately introduce mutations into homologous chromosomal target sequences (19). This process occurs in ∼1/10 4 hepatocytes after in vivo vector delivery to the liver (20,21). We reasoned that this gene-targeting frequency would be adequate to initiate multiple foci of HCC because of dysregulated gene expression after targeted promoter-enhancer insertion.…”
mentioning
confidence: 98%
“…This trend is also true in skeletal muscle (35, 60, 76), cardiac tissue (53, 68, 76), pancreas (72), and glioblastoma (21), and specialized cells in brain and retina are preferentially transduced by AAV8 (5, 9). In many animal models, AAV8 has already proven to provide an enormous therapeutic potential (7,18,38,47,54,55,62), although translation of the exceptional performance of AAV8 to higher primates has been challenging (25,74,75). Application of AAV8 vectors in a clinical trial has recently provided successful proof of concept for expression of the factor IX gene in human liver (48).…”
mentioning
confidence: 99%
“…Paulk et al, [103] demonstrated stable hepatic gene repair in both adult and neonatal mice with AAV-FAH serotypes 2 and 8, showing that AAV-mediated gene repair is feasible in vivo and can functionally correct enzymedeficiency consequences. In a study by Chen et al, [104] a murine model for hereditary tyrosinemia was used to evaluate in vivo gene therapy with AAV vectors expressing FAH.…”
Section: Tyrosinemiamentioning
confidence: 99%